Extended exp(-I(I)) -Expansion method for Solving the Generalized Hirota-Satsuma Coupled KdV System (Global Journal of Science Frontier Research, 2015)
In this research, The exact traveling wave solutions of the generalized Hirota-Satsuma couple KdV system is obtained as the first time in the framework of the extended exp('(_))expansion method. When these parameters are taken special values, the solitary wave solutions are derived from the exact traveling wave solutions. It is shown that the extended exp('(_))expansion method give a wide range of solutions and it provides an effective and a more powerful mathematical tool for solving nonlinear evolution equations in mathematical physics. Comparison between our results and the well-known results will be presented.
Keywords: the generalized hirota-satsuma coupled KdV system; the extended exp((_))- expansion method; traveling wave solutions; solitary wave solutions; ki